Architectuur en monument (Bulletin KNOB, 2010)
The relation between architectural history and heritage is ambiguous. Both domains are confronted with rapid changes in scale and complexity, leaving practitioners in both fields with the challenging task to provide new methods and a new vocabulary to enable research and communication. 70 years ago Nicolaus Pevsner could write about Lincoln cathedral and the bicycle shed to discern between architecture and building. These days not only housing and urban development have been accepted as ‘objects’ of research, in fact all material manifestation of human occupation, at least as far as design is involved, is considered worth studying.On the heritage side, developments are comparable: horizontally and vertically the domain has been enlarged tremendously: from a collection of ‘diamonds’ to complete cities, to landscapes and structures. This is not only true for scale and layers, but also for cultural norms of quality. Cultural relativism requires that ‘beauty’ and ‘quality’ are defined in relation to the social group or culture they refer to. The logic that an elite determines what is good and what is right is challenged by the notion that popular taste is in principle equal.So what does this do to our museum collections and lists of protected monuments? The consequences for architectural history are not yet clear. Including new realities like digital design and new fields of practice like the virtual, the knowledge base and toolbox of the architectural historian has to expand beyond the Renaissance ideal of the ‘uomo universale’.